PROJECTION GROWTH TWO-WHEELED VEHICLES AT PT. ETERNAL DESIRE OF REPRESENTATIVES YOUR FAME WITH USE EQUALITY DIFFERENTIAL GROWTH MODEL POPULATION CONTINUOUS (EXPONENTIAL MODEL AND LOGISTIC MODEL) - Faustianus Luan; Oktovianus R. Sikas; Leonardus Frengky Obe; Natalius Nahak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
This research explains how to determine the growth model for two-wheeled vehicles entered and sold at PT. Hasjrat Abadi, representative of Kefamenanu. The author uses data obtained from PT. Hasjrat Abadi representing Kefamenanu from 2019 – 2022. This research aims to apply the Differential Equation model Continuous Exponential Model and Logistic Model which are used to predict the growth rate of two-wheelers entered and sold at PT. Eternal Passion of the Ministry of Famennanu Representative . The results of this research show that the exponential III model is the most accurate for predicting the number of vehicles in 2025 in the form of a vehicle equation with a relative growth rate of 21% for incoming vehicles while vehicles with a relative growth rate of 21% per year. In the logistic model, the logistic model I is the most accurate for predicting the number of vehicles coming in and sold in 2025 which will be as many vehicles coming in as the number of vehicles being sold while the number of vehicles being sold . Based on the calculation results of the two models, which has the smallest error (the best model) in predicting the number of two-wheeled vehicles entered and sold at PT. The Kefamenanu Representative's eternal desire in 2025 is a logistics model.